MANAGEMENT BEHAVIOUR TESTING: RELATIONSHIP OF NON-PERFORMING LOAN AND OPERATIONAL EFFICIENCY RATIO IN THE INDONESIA BANKING SECTOR - Erlangga Ludwian, Reza
The high degree of competition and the presence of foreign banks, the problem of banking efficiency and stability are extremely significant from a microeconomic standpoint, and it should be high on the agenda to downsize underperforming institutions. The efficiency of the banking sector, on the other hand, has a significant impact on intermediary costs and preserving the banking system's stability since it may have systemic effects from a macroeconomic standpoint. This paper seeks to expand on prior research on management behaviour conducted by Berger and DeYoung (1992) in the context of the Indonesian banking industry in 4 different ownership clusters by examining the relationship between the NPL ratio and bank operational efficiency, which is specifically proxied by the non-interest expense/non-interest income in the Indonesian banking industry. The authors add to the wide body of knowledge by examining non-performing loans (NPLs) and bank efficiency in banks with varied ownership structures, notably in Indonesia. To the best of the author's knowledge, this article is the first to examine the management behaviour framework in the Indonesian banking system from the perspective of operational efficiency.